Genesis of an emergency public drug information website by the French Society of Pharmacology and Therapeutics during the COVID‐19 pandemic. (8th June 2020) - Larrouquere, Louis; Gabin, Manon; Poingt, Emmanuelle; Mouffak, Amelle; Hlavaty, Alex; Lepelley, Marion; Khouri, Charles; Bellier, Alexandre; Alexandre, Joachim; Bedouch, Pierrick; Bertoletti, Laurent; Bordet, Regis; et al.
Abstract: On March 16, 2020, the French Society of Pharmacology and Therapeutics put online a national Question and Answer (Q&A) website, https://sfpt-fr.org/covid19 on the proper use of drugs during the COVID‐19 pandemic. The working group 'Drugs and COVID‐19' was composed of a scientific council, an editorial team, and experts in the field. The first questions were posted online during the first evening of home‐confinement in France, March 17, 2020. Six weeks later, 140 Q&As have been posted. Questions on the controversial use of hydroxychloroquine and to a lesser extent concerning azithromycin have been the most consulted Q&As. Q&As have been consulted 226 014 times in 41 days. This large visibility was obtained through an early communication on Twitter, Facebook, traditional print, and web media. In addition, an early communication through the French Ministry of Health and the French National Agency for Medicines and Health Products Safety ANSM had a large impact in terms of daily number of views. There is a pressing need to sustain a public drug information service combining the expertise of scholarly pharmacology societies, pharmacovigilance network, and the Ministry of Health to quickly provide understandable, clear, expert answers to the general population's concerns regarding COVID‐19 and drug use and to counter fake news.